2019
DOI: 10.1186/s12943-019-1090-3
|View full text |Cite
|
Sign up to set email alerts
|

AXL receptor tyrosine kinase as a promising anti-cancer approach: functions, molecular mechanisms and clinical applications

Abstract: Molecular targeted therapy for cancer has been a research hotspot for decades. AXL is a member of the TAM family with the high-affinity ligand growth arrest-specific protein 6 (GAS6). The Gas6/AXL signalling pathway is associated with tumour cell growth, metastasis, invasion, epithelial-mesenchymal transition (EMT), angiogenesis, drug resistance, immune regulation and stem cell maintenance. Different therapeutic agents targeting AXL have been developed, typically including small molecule inhibitors, monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
342
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 347 publications
(352 citation statements)
references
References 259 publications
(314 reference statements)
8
342
2
Order By: Relevance
“…For example, TAM receptors are a type of indirect PS receptors, and growth arrest-specific 6 (Gas6) and Protein S are bridging molecules that facilitate the binding of PS on apoptotic cells to TAM receptors (Tyro3, Axl and MerTK) on phagocytes [37]. Further, Gas 6 binds to all three receptors, while Protein S only binds to Tyro3 and MerTK [38]. Milk fat globule epidermal growth factor-8 (MFG-E8) bridges between PS and α v β 3 /α v β 5 integrins, another type of indirect PS receptors [39].…”
Section: Engulfmentmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, TAM receptors are a type of indirect PS receptors, and growth arrest-specific 6 (Gas6) and Protein S are bridging molecules that facilitate the binding of PS on apoptotic cells to TAM receptors (Tyro3, Axl and MerTK) on phagocytes [37]. Further, Gas 6 binds to all three receptors, while Protein S only binds to Tyro3 and MerTK [38]. Milk fat globule epidermal growth factor-8 (MFG-E8) bridges between PS and α v β 3 /α v β 5 integrins, another type of indirect PS receptors [39].…”
Section: Engulfmentmentioning
confidence: 99%
“…Axl is typically activated by the Gas6 ligand, and the affinity of Gas6 for Axl is higher than to Tyro3 and MerTK receptors [62]. The Gas6/Axl signaling pathway influences cancer development and progression through its effect on tumor cell proliferation, invasion, metastasis, epithelialmesenchymal transition (EMT), and angiogenesis [38,63,64]. A previous study demonstrated that Axl is required for EMT, which promotes metastasis of HER-2 positive breast cancer [65].…”
Section: Tam Receptorsmentioning
confidence: 99%
See 3 more Smart Citations